Sacred Groves as Ethnobotanical Gene Pools in Tribal Area of the Western Himalaya in India - Thaplyal, Vandana; Sharma, Sanjeev; Bhatt, Ajay Ballabh (Indian Forester, 2012)
Study of sacred groves of Kinnaur district, based on the field survey, using GPS, topo sheets and village maps, supported with questionnaire survey in 17 sacred groves revealed the presence of 96 plant species of ethnobotanical importance within 77 genera and 41 families, representing 10 gymnosperms and 86 angiosperms. The species distributed as 22 trees, 32 shrubs and 42 herbs. As per the IUCN standards, 15 species are endangered, 17 are vulnerable and 6 are critically endangered.